2023
DOI: 10.1186/s12913-023-09035-0
|View full text |Cite
|
Sign up to set email alerts
|

Association of Medicaid expansion and 1115 waivers for substance use disorders with hospital provision of opioid use disorder services: a cross sectional study

Abstract: Introduction Opioid-related hospitalizations have risen dramatically, placing hospitals at the frontlines of the opioid epidemic. Medicaid expansion and 1115 waivers for substance use disorders (SUDs) are two key policies aimed at expanding access to care, including opioid use disorder (OUD) services. Yet, little is known about the relationship between these policies and the availability of hospital based OUD programs. The aim of this study is to determine whether state Medicaid expansion and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…First, because the Census of Governments data used in our analysis includes years in which there was a limited census conducted (2018–2020), the counties included may be subject to selection bias; however, we do include on year of data (2017) in which a full survey was conducted, which is a strength to this analysis. Second, while the GEE model accounts for time and intra-unit correlation effects, we do not include data on the implementation of state policies (i.e., Medicaid 1115 waivers for substance use disorders or Good Samaritan laws) [ 38 ] which may affect overdose risk in communities. Third, the fines and forfeitures data taken from the Census of Governments do not include other court costs, such as fees for jail time, and is likely an underestimation of the effect.…”
Section: Discussionmentioning
confidence: 99%
“…First, because the Census of Governments data used in our analysis includes years in which there was a limited census conducted (2018–2020), the counties included may be subject to selection bias; however, we do include on year of data (2017) in which a full survey was conducted, which is a strength to this analysis. Second, while the GEE model accounts for time and intra-unit correlation effects, we do not include data on the implementation of state policies (i.e., Medicaid 1115 waivers for substance use disorders or Good Samaritan laws) [ 38 ] which may affect overdose risk in communities. Third, the fines and forfeitures data taken from the Census of Governments do not include other court costs, such as fees for jail time, and is likely an underestimation of the effect.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study showed that the acceptance of Medicaid increased at residential and intensive outpatient facilities, and the delivery of medications increased with the adoption of the IMD exclusion waivers (13). It was also found that hospitals in states that have adopted Medicaid 1115 waivers for SUDs were more likely to provide opioid use disorder (OUD) treatment programs (14). By the end of 2020, there were 28 states with these SUD IMD Exclusion waivers (15).…”
Section: Introductionmentioning
confidence: 99%